Validation of cardiac diffusion tensor imaging sequences: A multicentre test–retest phantom study. (8th February 2022) - Teh, Irvin; Romero R., William A.; Boyle, Jordan; Coll‐Font, Jaume; Dall'Armellina, Erica; Ennis, Daniel B.; Ferreira, Pedro F.; Kalra, Prateek; Kolipaka, Arunark; Kozerke, Sebastian; Lohr, David; Mongeon, François‐Pierre; et al.
Abstract : Cardiac diffusion tensor imaging (DTI) is an emerging technique for the in vivo characterisation of myocardial microstructure, and there is a growing need for its validation and standardisation. We sought to establish the accuracy, precision, repeatability and reproducibility of state‐of‐the‐art pulse sequences for cardiac DTI among 10 centres internationally. Phantoms comprising 0%–20% polyvinylpyrrolidone (PVP) were scanned with DTI using a product pulsed gradient spin echo (PGSE; N = 10 sites) sequence, and a custom motion‐compensated spin echo (SE; N = 5) or stimulated echo acquisition mode (STEAM; N = 5) sequence suitable for cardiac DTI in vivo. A second identical scan was performed 1–9 days later, and the data were analysed centrally. The average mean diffusivities (MDs) in 0% PVP were (1.124, 1.130, 1.113) x 10 −3 mm 2 /s for PGSE, SE and STEAM, respectively, and accurate to within 1.5% of reference data from the literature. The coefficients of variation in MDs across sites were 2.6%, 3.1% and 2.1% for PGSE, SE and STEAM, respectively, and were similar to previous studies using only PGSE. Reproducibility in MD was excellent, with mean differences in PGSE, SE and STEAM of (0.3 ± 2.3, 0.24 ± 0.95, 0.52 ± 0.58) x 10 −5 mm 2 /s (mean ± 1.96 SD). We show that custom sequences for cardiac DTI provide accurate, precise, repeatable and reproducible measurements. Further work in anisotropic and/or deforming phantoms is warranted. Abstract : There is a growing need for validation of pulse sequences for cardiac diffusion tensor imaging (DTI). We show, in a multicentre study involving 10 sites, that custom sequences for cardiac DTI based on motion‐compensated spin echo and stimulated echo acquisition mode provide accurate, precise and reproducible measurements.